Pengaruh Earning Per Share (EPS), Return On Equity (ROE), Debt To Equity Ratio (DER) Terhadap Harga Saham Pada Perusahaan Sub Sektor Logam dan Sejenisnya Yang Terdaftar di Bei Periode 2017-2022 - Adi Purnomo (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research aims to determine the effect of EPS, ROE and DER on share prices partially and simultaneously. This type of research is carried out quantitatively with panel data and processed with statistical analysis assisted by E-Views and the appropriate model is Common Effect. The research population is companies in the metal and similar sub-sector. Sampling was carried out using purposive sampling and it was found that 5 research companies were carried out from the 2017-2022 period. The research results showed that EPS and ROE partially influenced share prices, but DER did not show a partial influence on share prices. Meanwhile, EPS, ROE and DER simultaneously influence share prices.